FINDING MEANING AND THE FUTURE: DIVING INTO THE NATURE AND PURPOSE OF ISLAMIC EDUCATION - Ulpah, Ghina; Basri, Hasan; Muslih, Hafid; Huda, Miftahul (LPPM STAI Muhammadiyah Probolinggo, 2024)
Islamic education is not just about the transfer of knowledge, but much more than that. It is about integrating the fundamental concepts of Islam, such as tawhid, treatise, morals, and science in harmony with religious values. The goal is not just to produce knowledgeable Muslims, but to form individuals with noble character based on Islamic values. This research explores the nature of Islamic education and its goals. Using qualitative methods and literature study, this research collects data from various sources such as books, news, and journals. These data are then analyzed to produce in-depth conclusions. The results show that Islamic education not only aims to provide knowledge about Islamic teachings, but also to form Muslim individuals who are role models in daily life. By understanding the nature and purpose of Islamic education, it is hoped that Muslim communities can produce generations that contribute positively to the development of the world and the hereafter in accordance with Islamic teachings.